Evaluation of the Surface Finish on 304 Stainless Steel as a Way to Mitigate Calcium Carbonate Scaling - Antônio Carlos Barbosa Zancanella; Luila Abib Saidler; Renato do Nascimento Siqueira; Helga Elisabeth Pinheiro Schluter; Bruno Venturini Loureiro (Surfaces)
Calcium carbonate scaling causes significant damage and financial losses to various industries, particularly in deep-water oil exploration. It is affected by factors like pressure, temperature, pH, solution chemistry, and surface finish. Surface finish is critical, as it interacts with the fluid and serves as a substrate for the anchoring of calcium carbonate crystals. However, many studies investigate this phenomenon under conditions that differ from those encountered in deep-water oil exploration. Tests are commonly performed under atmospheric pressure and lacking fluid flow or CO2 influence, which limits their relevance to industrial conditions. This study aims to evaluate the influence of surface finish on the formation of calcium carbonate scaling under conditions that more closely resemble actual operating environments. 304 stainless steel was selected to replicate industrial conditions, owing to its chemical stability and common use in industrial settings. The tests were conducted in a plant with high-pressure capabilities, operating under continuous flow conditions with CO2 injection. Controlled surfaces were prepared through metallographic polishing, machining, sandblasting, and laser texturing techniques. Surface characterization was performed using a 3D optical profilometer and scratch testing to measure the average adhesion force. The polymorphs formed were characterized by Raman spectroscopy. Fractal dimension analysis was applied to quantify the complexity of the analyzed surfaces. The results indicate that surfaces with higher fractal dimensions exhibit greater scaling mass and higher adhesion force. The main polymorph observed was calcite. Additionally, it was noted that the texture orientation relative to the flow affects scaling, with higher scaling values observed on surfaces oriented perpendicular to the flow. These findings are crucial for optimizing material selection and surface treatments in deep-water oil exploration, enhancing operational efficiency and reducing costs.